2024
DOI: 10.1021/acsanm.3c04784
|View full text |Cite
|
Sign up to set email alerts
|

Whey Protein Isolate-Based Aerogels with Improved Hydration Properties for Food Packaging Applications

Eleni Effraimopoulou,
József Kalmár,
Geo Paul
et al.

Abstract: In the present work, tannin-modified whey protein isolate (WPI/tannin) aerogels were synthesized, and their hydration properties were evaluated. The materials were prepared by introducing two different tannins (one hydrolyzable and one condensed) in the protein matrix via thermal-induced gelation of neutral or alkaline aqueous solutions (pH 7, 9, or 11) at 80 °C. WPI and WPI/tannin aerogels are nanostructured porous materials with high BET surface areas (216−353 m 2 g −1 ). Subsequently, WPI and WPI/tannin aer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 53 publications
0
0
0
Order By: Relevance
“…As a reference, the SEM image of a pure gelatin aerogel is also shown. The pristine gelatin aerogel (G) has a well-defined fibrillar structure, which is similar to that of whey protein aerogels. , However, the primary fibrils are entangled and interwoven due to the strong secondary interactions among the molecules of this structural protein. Chemically cross-linking the biopolymer highly influences the nanoscale morphology, resulting in a dense network of thick cylindrical bundles that are not characteristic of the pure gelatin aerogel.…”
Section: Resultsmentioning
confidence: 99%
“…As a reference, the SEM image of a pure gelatin aerogel is also shown. The pristine gelatin aerogel (G) has a well-defined fibrillar structure, which is similar to that of whey protein aerogels. , However, the primary fibrils are entangled and interwoven due to the strong secondary interactions among the molecules of this structural protein. Chemically cross-linking the biopolymer highly influences the nanoscale morphology, resulting in a dense network of thick cylindrical bundles that are not characteristic of the pure gelatin aerogel.…”
Section: Resultsmentioning
confidence: 99%
“…It was shown that in some cases, they can exhibit the characteristics of conventional aerogels such as low density and high specific surface area, as well as mesoporosity, and also possess the characteristics specific to bio-based polymers such as biodegradability and often biocompatibility. A wide range of bio-aerogels were obtained based on polysaccharides such as cellulose [ 11 , 12 , 13 ], chitosan [ 14 ], starch [ 15 , 16 ], alginate [ 17 , 18 ], pectin [ 19 , 20 , 21 ], proteins [ 22 , 23 ], or other polymers extracted from biomass [ 24 ]. Bio-aerogels are very attractive materials for a very wide variety of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Bio-aerogels are very attractive materials for a very wide variety of applications. These include thermal insulators [ 25 ], acoustic insulators [ 26 ], batteries’ electrodes [ 27 ], supercapacitors [ 28 ], piezoelectric transducers [ 29 ], CO 2 captures [ 30 ], absorbents [ 31 ], drug carriers [ 32 ], catalyst supports [ 33 ], and food packaging [ 22 ]. Several bio-aerogels were studied for their thermal insulation properties, and materials based on nanocellulose, starch, and pectin were shown to fall in the superinsulating area [ 16 , 21 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%